Laparoscopic paediatric surgery: A potential for paradigm shift in developing countries - M A Misauno; E O Ojo; A F Uba (Wolters Kluwer Medknow Publications, 2012)
Background: Until recently, surgical conditions in children requiring operation were managed by the traditional open method. The introduction of the laparoscopic surgical technique seems to be reversing this trend in many centres. We are pioneering some laparoscopic surgery procedures in our environment and the aim of this study was to document our experience with laparoscopic paediatric surgical procedures in a developing country. Materials and Methods: This was a prospective analysis of all consecutive children that had laparoscopic surgery at 5 hospitals in Northern Nigeria from June 2008 to February 2011. Results: Twenty-one patients had laparoscopic surgeries during the study period with a mean age of 12.5 ± 2.6 years and age range of 10-16 years. There were 14 females and 7 males with a M:F ratio of 1:2. Seven patients (33.3%) had cholecystectomies and 13 (61.9%) had appendicectomies and the remaining one patient (4.8%) had adhesiolysis for partial adhesive intestinal obstruction following previous open appendicectomy. The mean operating time was 89 min with a range of 45-110 min for appendicectomies, 55-150 min for cholecystectomies and the adhesiolysis took 50 min. The mean hospital stay was 2 days except for the conversions that stayed up to 7 days. There were 2 (9.5%) conversions with no mortality. Conclusion: We solicit a paradigm shift in our approach to surgical management and implore other centres to embrace laparoscopic surgery in the management of surgical conditions in children since it confers obvious advantages over open surgery.